Extraction of castor oil for (medical use) - Ayad M.R. Raauf; Cecilia K. Haweel; Mohammed S. Hammed (College of Pharmacy / Mustansiriyah University, 2009)
Extraction of castor oil for medical uses by cold press of castor beans at 38˚C with applied pressure 140 bars & pressing time of 70min., the maximum efficiency was found to be 80%. The pressed cake which contains 17% oil was subjected to solvent extraction with hexane under operation conditions: temperature, time of extraction and solvent to feed ratio. Bleaching of the castor oil with natural earth (bentonite) to improve the color.